SISTEM REKOMENDASI DAN PEMETAAN DESTINASI WISATA ALAM TERBAIK DI BERASTAGI MENGGUNAKAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) BERBASIS WEB - Nadya Syahfitri Damanik; Safwandi; Fajriana (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Berastagi is known as one of the favorite natural tourist destinations in North Sumatra that offers a variety of interesting tourist attractions. However, the many choices often make it difficult for tourists to determine the location that suits their preferences. This study aims to develop a web-based recommendation and mapping system for the best natural tourist destinations in Berastagi by implementing the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. This system considers six main criteria, namely ease of vehicle access, consumption costs, accommodation costs, security levels, and the availability of toilets and parking areas. Tourist locations are visualized through interactive maps based on Geographic Information Systems (GIS). Data were obtained from field surveys, interviews with visitors and managers, and location mapping using Google Maps. This system is specifically designed for three main user groups: independent tourists who want to plan their trips independently, local travel agencies who need data-based guidance to compile tour packages, and the district tourism office as a basis for decision making in promoting and developing regional tourism. System validation was carried out by comparing the recommendations given by the system with the actual choices of 20 respondents. From the results of this test, the system showed a match rate of 85%, with a p-value of 0.021. This figure shows that the recommendations from the system are quite in accordance with user preferences and have statistically significant results. Based on the analysis using the TOPSIS method, the five natural tourist destinations with the highest values ​​recommended by the system are: Lau Sidebuk-Debuk Hot Springs (0.694387), Mount Sibayak (0.648177), Sipiso-Piso Waterfall (0.644718), Gundaling Hill (0.636776), and Lau Kawar Lake (0.625521). This system is expected to be a guide that helps tourists plan trips more precisely, as well as support digital promotion of leading natural tourist attractions in the Berastagi area.